2013
DOI: 10.1371/journal.pone.0066984
|View full text |Cite
|
Sign up to set email alerts
|

Postural Abnormality as a Risk Marker for Leg Deep Venous Thrombosis in Parkinson’s Disease

Abstract: BackgroundPulmonary thromboembolism is a common cause of death in patients with autopsy-confirmed Parkinsonism. This study investigated the incidence of leg deep vein thrombosis in Parkinson’s disease and relationships between deep vein thrombosis and clinical/laboratory findings, including postural abnormalities as assessed by photographic measurements.MethodsThis cross-sectional study assessed the presence of deep vein thrombosis using bilateral leg Doppler ultrasonography in 114 asymptomatic outpatients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Seki et al reported that FB may cause severe constipation and urinary frequency [ 10 ]. A recent study by Yamane et al [ 17 ] showed that PD patients with FB and KB frequently have deep venous thrombosis of their lower extremities. With LB, patient can develop lumbar pain, dyspnea, unsteadiness leading to falls, or lower leg numbness due to radiculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Seki et al reported that FB may cause severe constipation and urinary frequency [ 10 ]. A recent study by Yamane et al [ 17 ] showed that PD patients with FB and KB frequently have deep venous thrombosis of their lower extremities. With LB, patient can develop lumbar pain, dyspnea, unsteadiness leading to falls, or lower leg numbness due to radiculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Camptocormia produces many negative consequences such as self-embarrassment or postural instability, whereas respiratory compromise is still controversial. 66 A recent study conducted by Yamane et al 67 showed that patients with PD with camptocormia frequently have deep venous thrombosis of their lower extremities when compared with PD without camptocormia (17% vs 4%, respectively).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…DVTs were noted in 20% of the patients with significantly increased knee and spine bending angles. In conclusion the study indicated that Parkinson's patients have decreased mobility due to motor abnormalities, which leads to an increased risk of thrombosis [9]. In patients with Shy-Drager syndrome, in addition to decreased mobility from Parkinsonism features, another feature which might contribute to venous thromboembolism is the presence of orthostatic hypotension, which can lead to pooling and stasis of the blood in the lower extremities, thereby increasing the risk of thrombosis.…”
Section: Discussionmentioning
confidence: 78%